2022
DOI: 10.1073/pnas.2120326119
|View full text |Cite
|
Sign up to set email alerts
|

Complex decay dynamics of HIV virions, intact and defective proviruses, and 2LTR circles following initiation of antiretroviral therapy

Abstract: Significance In persons living with HIV-1 who start antiretroviral therapy, virus in the blood decreases rapidly to below the detection limit. The decrease occurs in two phases: a rapid initial decrease in the first weeks, followed by a second, slower phase occurring over the next few months. These decay processes are important because infected cells that remain may become part of the stable latent reservoir that prevents cure. The decay in virus levels in blood presumably reflects the loss of infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
69
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 91 publications
(186 reference statements)
10
69
1
Order By: Relevance
“…Instead, our estimate of the mean lifespan of a productively infected cell (1/ δ ) is effectively a weighted average of the mean lifespans of all productively-infected subpopulations. Our estimate (16 days) is consistent with the median lifespan of 17 days we estimated previously from the VL dynamics in a subset of these infants who achieved suppression [ 4 ], and roughly in line with a recent estimate of the loss rate of infected CD4 T cells with intact proviruses [ 35 ]. Second, we do not explicitly model the dynamics of latently infected cells as they are not directly observed.…”
Section: Discussionsupporting
confidence: 91%
“…Instead, our estimate of the mean lifespan of a productively infected cell (1/ δ ) is effectively a weighted average of the mean lifespans of all productively-infected subpopulations. Our estimate (16 days) is consistent with the median lifespan of 17 days we estimated previously from the VL dynamics in a subset of these infants who achieved suppression [ 4 ], and roughly in line with a recent estimate of the loss rate of infected CD4 T cells with intact proviruses [ 35 ]. Second, we do not explicitly model the dynamics of latently infected cells as they are not directly observed.…”
Section: Discussionsupporting
confidence: 91%
“…Even more concerning is the fact that for two participants (P10 and P11), no intact proviruses were detected at the first time point (1–9 months after ART initiation). Although sampling issues or a very low frequency of intact provirus could explain these results, previous studies have shown that intact proviruses make up the majority of proviruses during early ART suppression [ 40 ], and large-scale studies with the IPDA rarely identify subjects for whom no intact proviruses are present [ 33 ]. Multiplexing of four qPCRs could reduce the sensitivity of individual primer-probe sets that have a dim fluorophore and lower efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Intact HIV-1 proviruses which have the potential to support viral rebound, have been estimated to represent 2-5% of the persistent provirus pool as measured in peripheral blood mononuclear cells (PBMCs) [8,9]. Longitudinal tracking of intact provirus sequences in PLWH before and after ART initiation suggests that most of the latent intact HIV reservoir has been seeded at the time of ART initiation and there is no additional infection post-ART [30][31][32], although ART initiation has been suggested to shape the latent reservoir [30][31][32]. It has also been suggested that the virus circulating at the time of ART initiation is overrepresented in the reservoir [30].…”
Section: Defective Hiv-1 Genomes Dominate the Proviral Landscapementioning
confidence: 99%